Studie av introduktionen av NorFor Plan för foderstatsberäkning till mjölkkor i Sverige - Åkerlund, Helena (2008)
NorFor is a cooperative project between the consulting organisations owned by the farmers in the Nordic countries – Sweden, Norway, Denmark and Iceland. The project started in 2001 and the outcome, the system for ration calculation NorFor Plan and the model for evaluating the ration NorFor Evaluation, was completed in 2006. Along with NorFor Plan economical optimization are available and according to literature, the optimization will generate a 2 öre lower feed cost per kg milk, and thereby improve the profit for the farmer. The use of NorFor Plan in Sweden for feed optimization during spring 2008 has been very small. In this study eight herds in the middle of Sweden fed half the herd according to the classical system used in Sweden and the other half according to NorFor Plan system. The milk production and feed consumption was compared between the groups. The results shows that there are great differences between herds, but the groups have been fed for equal production and with the same amount of energy and protein (measured as in the classic system). The cows fed according to NorFor Plan consumed 1.5 kg more roughage (p <0.0001) and 1 kg less concentrate (p=0.0001) than cows fed according to the classical system. The consequences were that cows fed according to NorFor Plan produced 1.6 kg less ECM (p=0.033) than the other group and the economical profit per cow for the NorFor-cows were 3.30 kr lower (p=0.0435), but the economical profit per kg milk were not changed. The conclusions are that cows fed according to NorFor Plan consume more roughage and less concentrate and that the milk production was negatively affected. The economical profit per cow is negatively affected but the economical profit per kg milk is unchanged. NorFor är ett nordiskt samarbetsprojekt mellan de lantbrukarägda rådgivningsorganisationerna i Sverige, Norge, Danmark och Island. Projektet påbörjades 2001 och 2006 var fodervärderingssystemet NorFor Plan och utvärderingsmodellen NorFor Evaluering klar. NorFor Plan är den ...